Optimization for customized trajectories in cone beam computed tomography - Hatamikia, Sepideh; Biguri, Ander; Kronreif, Gernot; Kettenbach, Joachim; Russ, Tom; Furtado, Hugo; Shiyam Sundar, Lalith Kumar; Buschmann, Martin; Unger, Ewald; Figl, Michael; Georg, Dietmar; Birkfellner, Wolfgang (Medical physics, 2020)
Purpose We developed a target-based cone beam computed tomography (CBCT) imaging framework for optimizing an unconstrained three dimensional (3D) source-detector trajectory by incorporating prior image information. Our main aim is to enable a CBCT system to provide topical information about the target using a limited angle noncircular scan orbit with a minimal number of projections. Such a customized trajectory should include enough information to sufficiently reconstruct a particular volume of interest (VOI) under kinematic constraints, which may result from the patient size or additional surgical or radiation therapy-related equipment. Methods A patient-specific model from a prior diagnostic computed tomography (CT) volume is used as a digital phantom for CBCT trajectory simulations. Selection of the best projection views is accomplished through maximizing an objective function fed by the imaging quality provided by different x-ray positions on the digital phantom data. The final optimized trajectory includes a limited angular range and a minimal number of projections which can be applied to a C-arm device capable of general source-detector positioning. The performance of the proposed framework is investigated in experiments involving an in-house-built box phantom including spherical targets as well as an Alderson-Rando head phantom. In order to quantify the image quality of the reconstructed image, we use the average full-width-half-maximum (FWHMavg) for the spherical target and feature similarity index (FSIM), universal quality index (UQI), and contrast-to-noise ratio (CNR) for an anatomical target. Results Our experiments based on both the box and head phantom showed that optimized trajectories could achieve a comparable image quality in the VOI with respect to the standard C-arm circular CBCT while using approximately one quarter of projections. We achieved a relative deviation <7% for FWHMavg between the reconstructed images from the optimized trajectories and the standard C-arm CBCT for all spherical targets. Furthermore, for the anatomical target, the relative deviation of FSIM, UQI, and CNR between the reconstructed image related to the proposed trajectory and the standard C-arm circular CBCT was found to be 5.06%, 6.89%, and 8.64%, respectively. We also compared our proposed trajectories to circular trajectories with equivalent angular sampling as the optimized trajectories. Our results show that optimized trajectories can outperform simple partial circular trajectories in the VOI in term of image quality. Typically, an angular range between 116° and 152° was used for the optimized trajectories. Conclusion We demonstrated that applying limited angle noncircular trajectories with optimized orientations in 3D space can provide a suitable image quality for particular image targets and has a potential for limited angle and low-dose CBCT-based interventions under strong spatial constraints.
Gesehen am 17.02.2025